The Influence of Conventional or KOBO Extrusion Process on the Properties of AZ91 (MgAl9Zn1) Alloy - Piotr Długosz (MDPI AG, 2021)
Designers’ efforts to use the lightest possible materials with very good mechanical properties mean that in recent years magnesium alloys have been increasingly used. It is well-known that the use of various plastic working processes allows achieving even better strength properties of the material, often without significant loss of plastic properties in relation to the properties of products obtained in the casting process. The article presents the results of research on microstructural changes and mechanical properties of the alloy AZ91 (MgAl9Zn1) occurring in samples subjected to conventional plastic deformation and the KOBO method. The obtained results were compared to the properties of reference samples, i.e., cast samples. The article presents the advantage of using the low-temperature KOBO method compared to the high-temperature deformation in a conventional manner. Moreover, it has been shown that the use of KOBO extrusion allows the alloy AZ91 (MgAl9Zn1) to obtain superplasticity properties with an elongation of up to 577% compared to the cast reference sample, which is generally classified as difficult for plastic deformation.